Unraveling successful company organizations: A research design to explore strategies for thriving amid market turbulence - Markus Niehaus; Katrin Hansen; Marian Mocan; Darius Barmayoun (Administrative Sciences, 2023)
Companies operate in ever faster and more abruptly changing environments. Due to the global interconnectedness of markets and actors, changes in framework conditions often have impacts across industries and geographical borders and constantly present companies worldwide with new challenges; however, they also offer opportunities. Adaptability to abruptly changing conditions and the ability to shape market environments have gained enormous importance as strategic factors for company organizations. How exactly can adaptability be shaped? This paper assumes that today's companies need concepts that help them to successfully adapt to these turbulent business environments and ideally to shape the changes to their own advantage. In addition, this work assumes that companies rely on already established models from science and business, but also (especially currently) develop new ideas themselves to adapt even faster and more effectively to changing conditions. To explore these phenomena, this paper develops a research funnel that can be used to identify companies that are most likely to provide answers to this question. In addition, this paper presents a research design with which the secrets of the adaptability of these companies can be explored in the field.
Keywords: 350; company organization; market turbulence; rapidly changing business environments; adaptability; organizational capabilities; field research; research funnel; research design